Pendekatan Diagnosis Tuberkulosis Kutis Verukosa: Tinjauan Pustaka - Ayuning Tasyqiya; Lusiana Lusiana; Sofa Inayatullah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and remains a global health problem, particularly in developing countries. One form of extrapulmonary TB is cutaneous tuberculosis, with the most common variant being tuberculosis verrucosa cutis (TBVC). Tuberculosis cutis verrucosa represents an exogenous reinfection in individuals who have been previously sensitized to the tubercle bacilli, and it typically presents as a chronic verrucous plaque that slowly evolves with centrifugal expansion. The diagnosis of TBVC is established through a multimodal approach, including history taking, physical examination, histopathological findings of tuberculoid granulomas, tuberculin skin test, interferon-gamma release assay (IGRA), polymerase chain reaction (PCR), and culture. Ziehl–Neelsen staining and culture often yield negative results due to the paucibacillary nature of the lesion; therefore, correlation between clinical features and supporting examinations remains essential for diagnostic confirmation. With a comprehensive clinical and diagnostic approach, the management of TBVC can be carried out more effectively.